A Comprehensive Systematic Review of Depression and Anxiety in Adults with Pyoderma Gangrenosum - Isnawati; Sri Siswanti; Masrida Rezky Ritonga (International Medical Journal Corp. Ltd, 2024)
Background: Pyoderma gangrenosum (PG) is a rare, chronic inflammatory skin disease characterized by painful, necrotic ulcers that frequently lead to disfiguring scars and significantly impact patients’ quality of life. This interplay between PG and mental health issues like anxiety and depression underscores the need for holistic approaches to manage both the physical and psychological challenges faced by PG patients. Methods: This systematic review adhered to the PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2015 and 2024. Result: A total of over 600 publications were initially identified through the database search. Following a rigorous three-stage screening process, eight studies were selected for comprehensive analysis. These studies were critically examined to provide an in-depth evaluation of depression and anxiety among adults with pyoderma gangrenosum. Conclusion: Pyoderma gangrenosum, a chronic autoimmune disorder, significantly impacts patients' mental health due to painful ulcers, visible lesions, and social isolation. Untreated depression can exacerbate pain perceptions and reduce treatment satisfaction. Healthcare providers must screen for and address mental health conditions in PG patients, utilizing psychological support and counseling to address both physical and mental health issues.